Arachidonic acid impairs hypothalamic leptin signaling and hepatic energy homeostasis in mice. (5th September 2015) - Cheng, Licai; Yu, Yinghua; Zhang, Qingsheng; Szabo, Alexander; Wang, Hongqin; Huang, Xu-Feng
Highlights: Arachidonic acid (ARA) can induce hypothalamic leptin resistance. Leptin JAK2-STAT3 and Akt-FOXO1 signalling in the hypothalamus is impaired by ARA. ARA elevates pro-inflammatory cytokines in the hypothalamus. ARA blunts the central leptin regulation of hepatic glucose and lipid metabolism. ARA attenuates the elevation of hypothalamic TH stimulated by leptin. Abstract: Epidemiological evidence suggests that the consumption of a diet high in n-6 polyunsaturated fatty acids (PUFA) is associated with the development of leptin resistance and obesity. We aim to examine the central effect of n-6 PUFA, arachidonic acid (ARA) on leptin sensitivity and leptin-regulated hepatic glucose and lipid metabolism. We found that intracerebroventricular injection of ARA (25 nmol/day) for 2.5 days reversed the effect of central leptin on hypothalamic JAK2, pSTAT3, pAkt, and pFOXO1 protein levels, which was concomitant with a pro-inflammatory response in the hypothalamus. ARA also attenuated the effect of central leptin on hepatic glucose and lipid metabolism by reversing the mRNA expression of the genes involved in gluconeogenesis (G6Pase, PEPCK), glucose transportation (GLUT2), lipogenesis (FAS, SCD1), and cholesterol synthesis (HMG-CoA reductase). These results indicate that an increased exposure to central n-6 PUFA induces central cellular leptin resistance with concomitant defective JAK2-STAT3 and PI3K-Akt signaling.